2019
DOI: 10.3390/agronomy9070389
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Solution Strength Does Not Interact with the Daily Light Integral to Affect Hydroponic Cilantro, Dill, and Parsley Growth and Tissue Mineral Nutrient Concentrations

Abstract: Our objectives were to quantify the growth and tissue mineral nutrient concentrations of cilantro (Coriandrum sativum 'Santo'), dill (Anethum graveolens 'Fernleaf'), and parsley (Petroselinum crispum 'Giant of Italy') in response to nutrient solution electrical conductivity (EC) under low and high photosynthetic daily light integrals (DLI). Three-week old seedlings of cilantro, dill, and parsley were transplanted into nutrient-film technique hydroponic systems with one of five nutrient solution EC treatments (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Reduced macronutrients have contributed to reduced growth at EC levels, as reported previously in hydroponics lettuce (Fallovo et al, 2009;Samarakoon et al, 2019). In herbs (Ocimum spp., Coriandrum sativum, Anethum graveolens, and Petroselinum crispum) grown in NFT systems, yield was not influenced by EC changes between 0.5 to 4.0 mS • cm -1 (Currey et al, 2019;Walters and Currey, 2018). In those studies, EC adjustments were done every day or automatically, and the tank size for the nutrient solution was double compared with our study.…”
Section: Discussionmentioning
confidence: 66%
“…Reduced macronutrients have contributed to reduced growth at EC levels, as reported previously in hydroponics lettuce (Fallovo et al, 2009;Samarakoon et al, 2019). In herbs (Ocimum spp., Coriandrum sativum, Anethum graveolens, and Petroselinum crispum) grown in NFT systems, yield was not influenced by EC changes between 0.5 to 4.0 mS • cm -1 (Currey et al, 2019;Walters and Currey, 2018). In those studies, EC adjustments were done every day or automatically, and the tank size for the nutrient solution was double compared with our study.…”
Section: Discussionmentioning
confidence: 66%
“…chinensis) increased; however, plants were only irrigated three times per week, and the hydroponic production system type is unknown (Ding et al, 2018). Additionally, high-wire tomatoes grown with ECs ranging from 2.5 to 5.0 dS • m -1 irrigated daily and NFT-grown culinary herbs with ECs from 0.5 to 4.0 dS • m -1 and daily pH and EC adjustment had similar fresh weight among EC treatments (Currey et al, 2019;Walters and Currey, 2018;Wu and Kubota, 2008). The authors hypothesize that EC may not limit growth when adjusted continuously but may become a limiting factor when nutrient solutions are adjusted periodically in recirculating systems.…”
Section: Resultsmentioning
confidence: 99%
“…A more consistent trend is observed between crops regarding nutrient uptake. For example, as EC increased, N concentration increased in pakchoi (Ding et al, 2018) and culinary herbs (Currey et al, 2019;Walters and Currey, 2018) and lycopene, fructose, glucose, and total soluble solids increased in tomato (Wu and Kubota, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that greatest growth was recorded at N:K 40:30, which also had a positive effect of the flowering parameters of pansy [ 45 ]. Currey et al [ 46 ] demonstrated that cilantro, dill, and parsley can be grown successfully in different ranges of EC levels in hydroponic cultivation.…”
Section: Discussionmentioning
confidence: 99%